2021
DOI: 10.7554/elife.65935
|View full text |Cite
|
Sign up to set email alerts
|

TRPM channels mediate learned pathogen avoidance following intestinal distention

Abstract: Upon exposure to harmful microorganisms, hosts engage in protective molecular and behavioral immune responses, both of which are ultimately regulated by the nervous system. Using the nematode Caenorhabditis elegans, we show that ingestion of E. faecalis leads to a fast pathogen avoidance behavior that results in aversive learning. We have identified multiple sensory mechanisms involved in the regulation of avoidance of E. faecalis. The G-protein coupled receptor NPR-1-dependent oxygen-sensing pathway opposes t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 74 publications
1
31
1
Order By: Relevance
“…On the microbe side, bacterial secondary metabolites and non-coding RNAs (Kaletsky et al, 2020) trigger the learned behavioral responsein the case of non-coding RNA even across multiple worm generations (Kaletsky et al, 2020). Interestingly, so far only pathogenic bacteria such as PA14, Serratia marcescens ATCC 13880 (Zhang et al, 2005;Zhang and Zhang, 2012), or Enterococcus faecalis (Filipowicz et al, 2021) were known to elicit the learned avoidance behavior. Ochrobactrum, however, has been repeatedly isolated from wild C. elegans and has positive or neutral effects on C. elegans life-history traits such as population growth (Zimmermann et al, 2020), animal growth rates, and body size (Dirksen et al, 2020;Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the microbe side, bacterial secondary metabolites and non-coding RNAs (Kaletsky et al, 2020) trigger the learned behavioral responsein the case of non-coding RNA even across multiple worm generations (Kaletsky et al, 2020). Interestingly, so far only pathogenic bacteria such as PA14, Serratia marcescens ATCC 13880 (Zhang et al, 2005;Zhang and Zhang, 2012), or Enterococcus faecalis (Filipowicz et al, 2021) were known to elicit the learned avoidance behavior. Ochrobactrum, however, has been repeatedly isolated from wild C. elegans and has positive or neutral effects on C. elegans life-history traits such as population growth (Zimmermann et al, 2020), animal growth rates, and body size (Dirksen et al, 2020;Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the colonization with MYb71 might lead to a gut distention provoking the late microbiota avoidance response. The learned pathogen avoidance response against E. faecalis is caused by its accumulation in the anterior worm gut mediated by two transient receptor potential melastatin channelseven with an attenuated pathogen (Filipowicz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic bacteria P. aeruginosa and E. faecalis are initially attractive to C. elegans and only induce an avoidance response after many hours of exposure [ 4 , 9 , 10 , 13 ]. This learning process involves the association of infection and subsequent physiological responses, including intestinal distention, engagement of RNAi pathways, and immune activation, with bacterial cues, resulting in avoidance of the bacteria [ 10 , 12 , 25 ]. Using the reflexive aversion assay, we found that naïve animals do not respond to drops of P. aeruginosa (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because we noticed a significant variation in the reflexive aversion of trained animals, we wondered whether varying levels of intestinal distention, which can trigger learned avoidance [ 10 , 25 ], accounted for the variation in the responses. Intestinal distention on P. aeruginosa , measured by either PA14-GFP signal in the intestinal lumen or intestine diameter, correlated with the trained response index to a weak, but significant, amount (Additional file 7 : Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation